2015
DOI: 10.1371/journal.pone.0133015
|View full text |Cite
|
Sign up to set email alerts
|

Two Mutations in the Caprine MTHFR 3'UTR Regulated by MicroRNAs Are Associated with Milk Production Traits

Abstract: Background5,10-Methylenetetrahydrofolate reductase (MTHFR) plays a central role in folate metabolism by irreversibly converting 5,10-methylenetetrahydrofolate to 5-methylenetetrahydrofolate, a predominant circulating form of folate. Folate is reportedly important for milk protein synthesis, and MTHFR may be a key regulatory point of folate metabolism for milk protein synthesis in mammary epithelial cells. Prior to this study, polymorphisms of the MTHFR gene were not associated with milk production traits from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…When the 14-bp indel in the 3 0 UTR of PRNP was inserted or deleted, the structure and function of genes related to the growth traits would be affected by bonding with miRNA. 31 In summary, an economic ME method was presented to quickly and accurately detect low frequency mutation, such as the 14-bp indel in the 3 0 UTR of the PRNP gene, which would save time and reduce expenses. Besides, the detected 14-bp indel significantly affect growth traits, which might be a potential useful DNA marker for MAS in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…When the 14-bp indel in the 3 0 UTR of PRNP was inserted or deleted, the structure and function of genes related to the growth traits would be affected by bonding with miRNA. 31 In summary, an economic ME method was presented to quickly and accurately detect low frequency mutation, such as the 14-bp indel in the 3 0 UTR of the PRNP gene, which would save time and reduce expenses. Besides, the detected 14-bp indel significantly affect growth traits, which might be a potential useful DNA marker for MAS in cattle.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that 3 UTR variants can affect gene transcription [49,50], and structural changes in the 3 UTR region are closely related to livestock and poultry production performance [51][52][53]. The 3 UTR is generally thought to regulate gene expression by affecting the stability of mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that mutations of basic sequences may alter mRNA stability, processing, and maturation, thereby affecting the allelic expression and co-translational folding pathway [46]. Predicting that the binding sites of transcription factors might exist in the PRNP indel loci, the expression of other growth-related genes would be influenced by bonding with miRNA [47]. For another, indel polymorphism in the 3 0 UTR could modulate traits or disease susceptibility via a microRNA- mediated post-transcriptional mechanism or elements of DNA functions [48].…”
Section: Discussionmentioning
confidence: 99%